2020
DOI: 10.21203/rs.3.rs-18651/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypertrophic pachymeningitis in a southern Chinese population: a retrospective study

Abstract: Background Hypertrophic pachymeningitis (HP) is a fibrotic disorder featuring a thickening of the dura matter. Most HP studies were from Caucasian population and only a few studies of HP are available in China. In this study, we investigated the causes, clinical and imaging features and therapeutic implications of HP in a southern Chinese population.Methods We retrospectively analyzed 48 patients with HP with different causes from 1 January 2006 to 31 December 2018. Clinical manifestation, laboratory findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Although patients with HP rarely had mononeuritis multiplex, which is also ascribable to small-to medium-sized vasculitis [4,29], the manifestations typically attributable to vasculitis might be little associated with HP development. It has been assumed that direct extension and/or transfer to the CNS from upper respiratory lesions, including granulomatosis inflammation, may be implicated in the mechanism for developing HP related to AAV [15,16,30]. Accordingly, our study also suggested that inflammatory lesions adjacent to the CNS, notably including eye and middle ear involvement, may be robustly implicated in HP development in AAV.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Although patients with HP rarely had mononeuritis multiplex, which is also ascribable to small-to medium-sized vasculitis [4,29], the manifestations typically attributable to vasculitis might be little associated with HP development. It has been assumed that direct extension and/or transfer to the CNS from upper respiratory lesions, including granulomatosis inflammation, may be implicated in the mechanism for developing HP related to AAV [15,16,30]. Accordingly, our study also suggested that inflammatory lesions adjacent to the CNS, notably including eye and middle ear involvement, may be robustly implicated in HP development in AAV.…”
Section: Discussionsupporting
confidence: 60%
“…Several single-center studies on ANCA-associated HP have been presented to date; however, it might be difficult to accurately determine the clinical characteristics contributing to HP development in AAV because of the limited number of patients analyzed at each institution. Considering the ethnic viewpoint of ANCA-associated HP, the majority of published studies have been reported from East Asian counties including Japan [8,10,[15][16][17][18][19][20]. Consequently, this was the first study to assess the clinical characteristics of HP using the enrolled information from many Japanese patients with AAV, demonstrating the epidemiological findings, especially the frequency of HP and classification in AAV, as more reliable results…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The most common neurological symptoms of patients suffering from IgG4-related hypertrophic pachymeningitis are headache and cranial nerves palsies, followed by motor or sensory deficits, seizures, and ataxia. Headache may reflect meningeal inflammation [2,34]. Cranial nerve palsies are usually due to compression by the thickened dura mater [4,23].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose methylprednisolone therapy (1 g/day for 3 days) has been recommended in patients with acute severe neurological deficits [2]. Another strategy is the concomitant use of immunosuppressive agents such as methotrexate (20 mg/ week), azathioprine (100-200 mg/day), mycophenolate mofetil (1000 mg twice daily), and cyclophosphamide (either oral 100 mg/day) [21,34]. In our series, adjuvant therapy was used as a steroid-sparing strategy in all instances.…”
Section: Discussionmentioning
confidence: 99%